PENYULUHAN POSISI ERGONOMIS SAAT BELAJAR DI SMA BATIK 1 SURAKARTA - Farid Rahman; Brissa Isabel Salsabila; Puji Eva Annisaa; Ina Hidayati; Karimatun Naim; Bangkit Dwi Prihantoro; Shandyka Trybuana; Arif Pristianto; Wahyuni Wahyuni (Rafandha Press, 2023)
The return of face-to-face learning in the midst of the Covid-19 pandemic deserves attention. In addition to continued attention to health protocols, students need to be reminded of the importance of ergonomic postures while studying. If left unchecked, it will have an impact on appearance, psychology and health, especially musculoskeletal disorders. The aim of this consultation is to prevent the occurrence of musculoskeletal disorders caused by incorrect posture while studying. This counselling activity was conducted in December 2022-January 2023 at SMA Batik 1 Surakarta. The method used was a lecture with a power point and supported by the provision of stretching exercise education with leaflets. The population in this extension activity was 77 students with the concept of community-based participatory research (CPR). The evaluation indicators were pre-test and post-test questionnaires on students' understanding of ergonomic postures while studying and students' complaints. The results showed that the number of students in the